Pengaruh Terapi Musik Gamelan Langgam Jawa Terhadap Tingkat Stres pada Lansia di Panti Pelayanan Sosial Lanjut Usia Sudagaran Kabupaten Banyumas - Meliyana, Asri; Kurniawan, Wasis Eko; Yanti, Linda (STIKES Suaka Insan, 2023)
Stress is the body's non-specific response to any load demand. Javanese style music therapy is designed to provide a detailed introduction to the client's situation and problem, a type of traditional Indonesian music that looks similar to keroncong. The purpose of this study was to determine the effect of Javanese gamelan music therapy on stress levels in the elderly. This type of research uses quantitative research with Pre-experiment method, type one group pretest-posttest design. The population in this study amounted to 90 people, all at the Sudagaran Elderly Social Service Institution. This research method uses simple random sampling as many as 20 respondents based on the Slovin formula. The results of the Wilcoxon signed rank test showed that the p-value was 0.000 <0.05 which indicated the influence of stress levels on the elderly before and after Javanese gamelan music therapy was performed at the Sudagaran Elderly Social Service Institution, Banyumas Regency. Javanese gamelan music therapy is effective in reducing stress levels in the elderly in nursing homes.